Boswell Cannery, B.C. Packers, Smith Sound ... - Hughes, E. J. Edward John, 1913-2007 (University of Victoria Libraries, 2023)
A graphite drawing by E. J. Hughes showing a view from a ship tied to a dock at the Boswell Cannery located at the now abandoned cannery town of Boswell on the north side of Boswell Inlet, an arm of Smith Sound. There are some notes on the sketch. ...